INFLUENCE OF VORTIOXETINE AND PIOGLITAZONE ON NEUROPHYSIOLOGICAL MANIFESTATIONS IN A RAT MODEL OF CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY - Kulynych, H.B.; Herashchenko, S.B.; Ostrovskyi, M.M.; Markiv, I.M.; Pertsovych, V.M.; Diachuk, O.I.; Tiron, O.I. (World of Medicine and Biology, 2025)
The purpose of the study was to evaluate the effects of vortioxetine and pioglitazone on the neurophysiological manifestations of chemotherapy-induced peripheral neuropathy in rats induced by paclitaxel, cisplatin, or their combination. The study investigated the neurophysiological manifestations of peripheral neuropathy induced by paclitaxel, cisplatin, or their combination, and evaluated the efficacy of vortioxetine (5 mg/kg) and pioglitazone (20 mg/kg) in their correction in a rat model. Von Frey (mechanical allodynia), hot plate (thermal hyperalgesia), and Rotarod (motor impairment) tests were conducted in 12 groups of animals (n=30) over 120 days. Chemotherapy induced an expressed allodynia and hyperalgesia, peaking at day 7. Prophylactic and therapeutic administration of vortioxetine and pioglitazone significantly reduced these manifestations by days 14–28. Motor impairments remained unaffected. The results suggest the potential of vortioxetine and pioglitazone for neuropathy correction.
Keywords: peripheral neuropathy; paclitaxel; cisplatin; vortioxetine; pioglitazone; mechanical allodynia; thermal hyperalgesia; rats